Multi-Level-Marketing shaping and supporting Brand Identity - Haldenmayr,Ina Katja; Kobylka,Daria; Tsoulou Vasilopoulou,Eirini Maria (2023)
Purpose: The purpose of this study is to assess potentially existing interdependencies between Brand Identity and a Multi-Level Marketing approach. Furthermore, the study aims to give theoretical and managerial recommendations for marketers as well as brand managers in order to make use of these interdependencies. The broader aim is to present the concept of Multi-Level Marketing that can be a valuable technique for not only boost awareness and sales, but also strengthen the Brand Identity. Methodology: Comparative analysis of MLM-strategies of selected brands and their effects, conducting an online-survey within the target group to examine effects on brand loyalty. Findings: Multi-Level Marketing can influence brand image and purchase decisions positively if the brand’s values and Brand Identity are associated with a high emphasis on relationships and trust. Under these prerequisites, which are not given in all industries, Multi-Level Marketing models can not only be effective in leveraging personal networks and building trust among consumers, contributing to brand loyalty and a strengthened Brand Identity, but also increase sales numbers. Original/Value: Many brands fail to implement cost-efficient marketing techniques that do not only increase sales, but also support and strengthen their Brand Identity. In this field, many concepts and theories can be found. However, the concept of MultiLevel Marketing got assessed primarily with a focus towards sales numbers or legal implications in previous research, not about its effects on Brand Identity and potential mutual catalyzing effects. This study aims to fill this gap and derive valuable recommendations for marketers as well as brand managers from it.
Keywords: Multi-level Marketing; Brand Identity; Brand Image; Social Networks; Purchasing Decisions